Health outcomes of patients with dementia in acute care settings—A systematic review. (24th March 2020) - Fox, Amanda; MacAndrew, Margaret; Ramis, Mary‐Anne
Abstract: Background: An ageing population has resulted in increased numbers of people with dementia attending acute care services; however, the impact of hospitalisation on this population is uncertain. Purpose: This systematic review aimed to synthesise the available evidence on adverse health outcomes for people with dementia in acute care settings. Methods: A systematic search of CINAHL, PubMed, MEDLINE, EMBASE and Scopus databases for primary research articles in English language, published from 2000 to 2017, was conducted. A protocol for the review was registered on the PROSPERO database. Results: The initial search identified 5, 520 records. Following removal of duplicates and assessment against inclusion criteria, 13 studies were included in the final review. Findings identify associations between patients with dementia, longer length of hospital stay and higher mortality in some situations. Heterogeneity across studies in data reporting and outcomes prevented meta‐analysis; therefore, results are presented narratively. Conclusions: Certainty of findings from this review is impacted by variation in patient condition and data reporting. Additional rigorous studies on health outcomes for people with dementia during acute hospitalisation will contribute to the evidence. Implications for practice: These findings along with further research examining outcomes for patients with dementia in acute care settings will inform provision of safer, quality care and optimal health outcomes for this vulnerable population.